Study of Co-and Ni-MCM-41 supported catalysts and effects of Pt promoter addition on carbon dioxide reforming of methane - Lim, Yvonne Yi Wen. (2010)
The catalytic performances of promoter-modified and un-modified bimetallic catalysts in CO2 reforming of methane were studied. Co and Ni metals were incorporated into mesoporous MCM-41 by direct hydrothermal synthesis, while promoter Pt was loaded by conventional wet impregnation. The structures and compositions of the fresh catalysts were characterized using various methods including X-ray powder diffraction, nitrogen physisorption and temperature programmed reduction. Monometallic Ni-based catalyst exhibited higher catalytic activity as compared to the Co counterpart over the entire temperature range tested. Subsequent Pt introduction improved the activity of both Co- and Ni-MCM-41, with Pt/Ni-MCM-41 leading ahead of the Co catalyst. Long-term stability of the catalysts was also investigated. Monometallic Co- and Ni-MCM-41 deactivated rapidly within the first 12 hours of reaction. Pt-impregnated bimetallic catalysts exhibited a distinctively improved stability in comparison to the monometallic catalysts, with low carbon deposition as characterized by thermogravimetric analysis. Synergetic interaction of Pt-Co and Pt-Ni alloys was proposed to be the cause of the lower carbon deposition which in turn ensured a stable catalytic level at an elevated temperature over a substantial period of time. The Pt-modified bimetallic catalysts, especially Pt/Ni-MCM-41, demonstrated excellent catalytic activity with high carbon resistivity and could prove to be promising catalysts for the CO2 reforming of methane.